“ZOONYMS IN CHILDREN’S POETIC LITERATURE: A CROSS-LINGUISTIC ECOLINGUISTIC AND AXIOLOGICAL STUDY IN ENGLISH, UZBEK, AND RUSSIAN” - Numonova, Mukharramkhon (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
This study investigates the use of zoonyms in children’s poetic literature across English, Uzbek, and Russian, focusing on their cognitive, axiological, and ecolinguistic functions. Drawing on Conceptual Metaphor Theory, axiological analysis, and ecolinguistics, the research analyzes a corpus of over 130 poems containing animal references. Zoonyms such as dogs, foxes, lions, camels, wolves, bears, and birds were examined for their representation of human traits, moral and cultural values, and ecological awareness. The findings reveal that certain animals convey universal traits, such as dogs representing loyalty and foxes representing cleverness, while others, such as camels in Uzbek poetry or bears in Russian poetry, reflect culture-specific values and environmental contexts. Across all three languages, animals serve as cognitive tools, moral educators, and ecological models, highlighting the interconnections between language, culture, and nature in children’s literature. This cross-linguistic analysis provides insights for educators, literary scholars, and curriculum designers aiming to foster moral reasoning, cultural understanding, and ecological awareness in young learners.